The Effectiveness Analysis Of Search, Solve, Create And Share (Sscs) Learning Model Implementation On Students’ Cognitive Ability - Ilham Kamaruddin; Irvan Irvan; Yoseb Boari; Bayu Purbha Sakti; Yance Manoppo (Mudir : Jurnal Manajemen Pendidikan, 2023)
The focus of this research is on the inadequate cognitive learning outcomes among high school students in the areas of rotation dynamics and balancing rigid bodies. The aim of this study is to investigate the impact of the search, solve, create, and share (SSCS) learning approach on students' cognitive abilities. A quasi-experimental research design with a non-equivalent control group was used as the research methodology. A purposeful sampling technique was employed to collect samples from 100 students. The hypothesis test conducted on the posttest data using the Mann-Whitney test at ????= 0.05 resulted in the rejection of H0 and acceptance of H1, with a sig. (2-tailed) value of 0.00. The SSCS learning approach has a significant impact on students' cognitive abilities. The experimental group demonstrated greater progress in their cognitive learning outcomes than the control group. Furthermore, students who applied the SSCS learning model were found to be 72% more engaged in their studies.